2018
DOI: 10.18261/issn.2535-2512-2018-03-05
|View full text |Cite
|
Sign up to set email alerts
|

Virtuelle grenseutfordringer

Abstract: Artikkelen undersøker hvordan brukere av dataspillet The League of Legends beskriver og forholder seg til symbolske grenser og identitetskonstruksjoner. Artikkelens analytiske og teoretiske rammeverk er inspirert av teorier om symbolske grenser. Analysen er sentrert rundt kulturelle distinksjoner, stereotyper og grensevoktende mekanismer og baserer seg på semi-strukturerte intervjuer med fem unge voksne spillere av begge kjønn, samt observasjoner av gruppen i spillsituasjoner og studier av spillet. Den viser h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Women players have utilised various strategies in response to the hostile environment of competitive gaming. A common strategy is known to be hiding their gender from other players, including choosing gender-neutral gamertags and not using microphone features, or using a voice changer for conversation (Arneberg and Hegna, 2018). However, revealing one's gender is unavoidable at a professional level, which might be an explanatory factor for the low participation of women in professional esports competitions.…”
Section: Previous Researchmentioning
confidence: 99%
“…Women players have utilised various strategies in response to the hostile environment of competitive gaming. A common strategy is known to be hiding their gender from other players, including choosing gender-neutral gamertags and not using microphone features, or using a voice changer for conversation (Arneberg and Hegna, 2018). However, revealing one's gender is unavoidable at a professional level, which might be an explanatory factor for the low participation of women in professional esports competitions.…”
Section: Previous Researchmentioning
confidence: 99%
“…Similarly, Arneberg and Hegna (2018) have identified gender stereotypes in the game League of Legends (LoL) and argue that 'girl gamers' is a stigmatised category that the girls do not want to be associated with. Jansz and Martens (2005) found that LAN gamers were almost exclusively males.…”
Section: Previous Researchmentioning
confidence: 99%